Prenatal prediction of significant intertwin birthweight discordance using standard second and third trimester sonographic parameters. (13th February 2017) - Hehir, Mark P.; Breathnach, Fionnuala M.; Hogan, Jennifer L.; Mcauliffe, Fionnuala M.; Geary, Michael P.; Daly, Sean; Higgins, John; Hunter, Alyson; Morrison, John J.; Burke, Gerard; Mahony, Rhona; Dicker, Patrick; et al.
Abstract: Introduction: Our study aim was to evaluate standard ultrasound‐derived fetal biometric parameters in the prediction of clinically significant intertwin birthweight discordance defined as ≥18%. Material and methods: This was a secondary analysis of a prospective cohort study of 1028 unselected twin pairs recruited over a two‐year period. Dichorionic twins underwent two‐weekly ultrasonographic surveillance from 24 weeks' gestation, with surveillance of monochorionic twins two‐weekly from 16 weeks. Ultrasonographic biometric data from 24 to 36 weeks were evaluated for the prediction of an intertwin birthweight discordance threshold ≥18%. Umbilical artery Doppler waveform data was also analyzed to evaluate whether it was predictive of birthweight discordance. Results: Of the 956 twin pairs analyzed for discordance, 208 pairs were found to have a clinically significant birthweight discordance ≥18%. All biometric parameters were predictive of significant inter‐twin birthweight discordance at low cut‐offs, with low discriminatory powers when ROC curves were analyzed. Discordance in estimated fetal weight was predictive of a significant birthweight discordance at all gestational categories with cut‐offs between 8 and 11%. A low‐discriminatory power and poor sensitivity and specificity were also observed. An abnormal umbilical artery Doppler was predictive of birthweight discordance ≥18% between 28 and 32 weeks' gestation, although with poor sensitivity and specificity. Conclusions: Calculation of estimated fetal weight and birthweight discordance between twins allows minimal margin for error. These margins make it difficult to accurately predict those who are at or above the discordance threshold of 18%. These findings highlight that small intertwin discrepancies in weight and biometry should not be overlooked and merit further investigation.